How Does The Nature and Understanding of Venture Philanthropy amongst Investment Professionals Relate to Its Impact as A Potential Form of Investment for Social Enterprise in the United Kingdom - Kidd, Anna (2007)
The Government of the United Kingdom (UK Government) believes that the third sector and in particular social enterprise has a key role to play in meeting key government targets for example in the areas of social need or regeneration of deprived areas. To meet these targets an increase in finance for the third sector and in particular social enterprise is necessary.